2013
DOI: 10.1177/193229681300700610
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Insulin Aspart and Glucagon in Type 1 Diabetes during Closed-Loop Operation

Abstract: Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 21 publications
6
23
0
Order By: Relevance
“…However, using literature informed prior distributions of both tmax and ClF,I and optimizing for all four visits simultaneously we obtained reasonable fits by MAP estimation [28,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, using literature informed prior distributions of both tmax and ClF,I and optimizing for all four visits simultaneously we obtained reasonable fits by MAP estimation [28,34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that a simple two-state model with identical time constants for absorption and elimination could be used to describe the PK of insulin aspart after SC dosing [28]. …”
Section: Insulin Pharmacokinetic Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The model used in the present study was previously employed to study insulin aspart pharmacokinetics in T1D [19,20]. Compared to T1D, t max is longer and MCR I lower in the present study investigating T2D.…”
Section: Fig 2 -Weighted Residuals (Median and Iqr) Representing Difmentioning
confidence: 96%
“…The exogenous plasma insulin concentration is obtained assuming instantaneous equilibration between insulin appearance in plasma and plasma insulin reflecting a short plasma insulin half-life relative to the frequency of plasma insulin measurements [19,20]:…”
Section: Insulin Kineticsmentioning
confidence: 99%